The Interaction and Acculturation of Islamic Law and Rejang Customary Law in Rejang Lebong Regency - Mabrursyah, Mabrursyah; Marhayati, Nelly; Habiburrahman, Habiburrahman; Yasmin, Anida; Yusro, Ngadri (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
The Rejang people are one of the ethnic groups inhabiting Bengkulu Province, possessing a unique language and script. Over time, it is suspected that interaction and acculturation have occurred between Islamic teachings and the customs of the Rejang people, with Islamic values exerting a significant influence on their way of life. The aim of this research is to identify the various types of customary law practiced by the Rejang people and to explore the interaction and acculturation between Islamic law and Rejang customary law in Rejang Lebong District. To achieve this goal, the study employed a normative empirical method with a qualitative approach, which included legal document analysis, as well as direct observation and interviews. The findings revealed two main conclusions: First, the types of Rejang customary law in Rejang Lebong District encompassed various rules within the categories of customary law such as cepalo mato, cepalo mulut, cepalo tangan, cepalo kaki, and cepalo telingo. These rules reflected strong values and norms that regulated individual behavior and social interactions within the community. In cases of more serious violations, such as adultery and immorality involving the abduction of another man’s wife, Rejang customary law enforced stricter measures such as flogging and cuci kampung (community cleansing rituals). Second, there was a mutual interaction between the universal values of Islam and the unique local customs, resulting in a distinctive form of Islamic culture. The process of acculturation between Islamic law and Rejang customary law created a unique form of Rejang customary law that did not conflict with the principles of Islamic law.